Incidence and Outcome of Group B Streptococcal Sepsis in Infants in Switzerland. Issue 2 (February 2016) - Giannoni, Eric; Berger, Christoph; Stocker, Martin; Agyeman, Philipp; Posfay-Barbe, Klara M.; Heininger, Ulrich; Konetzny, Gabriel; Niederer-Loher, Anita; Kahlert, Christian; Donas, Alex; Leone, Antonio; Hasters, Paul; et al.
Abstract : The incidence and outcome of group B streptococcal (GBS) sepsis were assessed prospectively between September 2011 and February 2015 in all tertiary care pediatric hospitals of Switzerland. We describe a low incidence of GBS early-onset sepsis (0.12/1000 livebirths) and a predominance of GBS late-onset sepsis (0.36/1000 livebirths), a pattern that has not been reported in other countries.